Pengembangan Media Papan Huruf untuk Meningkatkan Motivasi Belajar Siswa Kelas 1 SDN Natakupe: Development of Letter Board Media to Enhance Learning Motivation for 1st Grade Students at SDN Natakupe - Pare, Maria Ines Teresa; Beku, Veronika Yuliana; Dhiu, Maria Isabela; Sayangan, Yohanes Vianey (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to develop learning media in the form of a letterboard designed to increase the learning motivation of grade 1 students of SDN Natakupe, especially in learning Indonesian, and to test its feasibility. Student learning motivation is a major concern because it plays an important role in supporting an effective learning process. This research focuses on the question, "How feasible is the use of typeboard media as a learning tool in grade 1 elementary school?" The research uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subject of the study was a 1st grade student of SDN Natakupe. Data was collected through a survey involving material experts, media experts, design experts, and users, with instruments in the form of questionnaires that were validated quantitatively and qualitatively. Data analysis was carried out using descriptive statistical methods to determine the feasibility level of letterboard media. The results of the validation of the letterboard media showed that the aspects of practicality, aesthetics, and content suitability obtained an average score of 90% (very feasible), 87% (very feasible) media experts, and 80% (feasible) design experts. The trial on students generated a positive response, with an average score of 96% for increased attractiveness, ease of use, and motivation to learn. The use of this media not only attracts students' attention, but also increases their active involvement in the learning process through a play-by-play approach to learning. Letterboard media has proven to be effective as a learning tool and can be used as an alternative media to increase student learning motivation at the elementary school level. More research is needed to evaluate the effectiveness of this medium on a wider student population.